(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
A bronze tripod found near Hexham in Northumberland was exhibited. Albert Way suggests that this item may have been used as a ewer and could date from the fourteenth century. He notes that it is unusual for objects of this kind to have an inscription, but as he is unable to translate it, he is hesitant to draw many conclusions about the artefact. Meeting notes for 2 July, 1860 are appended. Included in the meeting notes are extensive descriptions of the donations presented on the day.